2013
DOI: 10.1002/bdd.1848
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐based prediction of human intestinal membrane permeability for rapid in silico BCS classification

Abstract: Human effective intestinal membrane permeability (Peff) is one of the two important indicators for drug classification according to the Biopharmaceutical Classification System (BCS), and contributes greatly to the performance of oral drug absorption. Here, a structure-based in silico predictive model of Peff was developed successfully to facilitate in silico BCS classification in the early stage of drug discovery, even before the compound was synthesized. The quantitative structure-Peff relationship for 30 dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…S5 (ESM), the non-toxic concentration for ergotamin(in)e was selected at 10 μg/mL and lower. Human studies have shown overall low oral bioavailability of ergotamine [45,46], and it has been classified to be a BCS III compound, meaning a low-permeability compound [47]. Therefore, we used the highest non-toxic concentration possible for the ergotamin(in)e permeability experiments (10 μg/mL).…”
Section: Ergotamin(in)ementioning
confidence: 99%
“…S5 (ESM), the non-toxic concentration for ergotamin(in)e was selected at 10 μg/mL and lower. Human studies have shown overall low oral bioavailability of ergotamine [45,46], and it has been classified to be a BCS III compound, meaning a low-permeability compound [47]. Therefore, we used the highest non-toxic concentration possible for the ergotamin(in)e permeability experiments (10 μg/mL).…”
Section: Ergotamin(in)ementioning
confidence: 99%
“…Extensive studies have been done to explore the transportation of drug-like compounds with computations, which provide valuable insights into the details at atomic level that cannot be accessed by experiments 17 20 . Among different descriptors for characterizing the permeability of drug-like compounds 21 23 , the partition coefficient (log P ) is the most commonly used one. Log P is defined as the logarithm of the ratio of compounds dissolved in lipid bilayers and the buffer water of a two-compartment system under equilibrium conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, among the most relevant high‐throughput methods for studying intestinal permeability and the oral absorption of drugs are the in silico approaches. Several quantitative structure–property relationships (QSPR) have been proposed for the prediction of human intestinal absorption, membrane permeability as well as for BCS classification (Kasim et al, ; Newby, Freitas, & Ghafourian, ; Pham‐The, González‐Álvarez et al, ; Pham‐The et al, ; Sun et al, ; Wolk, Agbaria, & Dahan, ). In silico models are inexpensive tools with a high‐throughput capacity, but their accuracy is limited by the quality of the raw in vivo data upon which they are based, the statistical approach and the kind of molecular descriptors used in the models.…”
Section: Discussionmentioning
confidence: 99%